2016
DOI: 10.1002/anie.201600224
|View full text |Cite
|
Sign up to set email alerts
|

Guided Self‐Propelled Leaping of Droplets on a Micro‐Anisotropic Superhydrophobic Surface

Abstract: By introducing anisotropic micropatterns on a superhydrophobic surface, we demonstrate that water microdroplets can coalesce and leap over the surface spontaneously along a prescribed direction. This controlled behavior is attributed to anisotropic liquid-solid adhesion. An analysis relating the preferential leaping probability to the geometrical parameters of the system is presented with consistent experimental results. Surfaces with this rare quality demonstrate many unique characteristics, such as self-powe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
98
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(100 citation statements)
references
References 33 publications
2
98
0
Order By: Relevance
“…[16][17][18][19] In addition to the dynamics of liquid bridge, there is now the added feature of the motion of a three-phase contact line. [23][24][25][26] Considerable efforts have been devoted to studying the reason for the inefficient conversion of released surface energy to translational kinetic energy during droplet jumping process. Recently, it is found that water droplets coalesce on the superhydrophobic surfaces (SHSs) can undergo self-propelled motion, which is called coalescence-induced droplet jumping.…”
Section: Introductionmentioning
confidence: 99%
“…[16][17][18][19] In addition to the dynamics of liquid bridge, there is now the added feature of the motion of a three-phase contact line. [23][24][25][26] Considerable efforts have been devoted to studying the reason for the inefficient conversion of released surface energy to translational kinetic energy during droplet jumping process. Recently, it is found that water droplets coalesce on the superhydrophobic surfaces (SHSs) can undergo self-propelled motion, which is called coalescence-induced droplet jumping.…”
Section: Introductionmentioning
confidence: 99%
“…investigated enhanced jumping of condensed water droplets by anti-icing surfaces. Liu et al 9. controlled self-propelled leaping of droplets along a prescribed direction on a micro-anisotropic superhydrophobic surface.…”
mentioning
confidence: 99%
“…By contrast, other animals and plants such as geckos 7 or red roses 8 are able to strongly attract water (high water adhesion) even if they are highly hydrophobic. This property is extremely interesting for water harvesting and transportation systems [9][10][11] or for actuation of underwater locomotion, 12,13 for example. Marmur proposed the use of the term parahydrophobic to distinguish this property from superhydrophobicity.…”
Section: Introductionmentioning
confidence: 99%